1985
DOI: 10.1128/jcm.22.5.740-744.1985
|View full text |Cite
|
Sign up to set email alerts
|

Rapid diagnosis of LaCrosse encephalitis: detection of specific immunoglobulin M in cerebrospinal fluid

Abstract: An immunoglobulin M (IgM) antibody capture enzyme immunoassay (MAC-EIA) was developed for the rapid and early diagnosis of LaCrosse (LAC) virus infections. The MAC-EIA was a sensitive and specific technique for the detection of IgM antibodies to LAC virus in cerebrospinal fluid specimens and in acute-phase serum specimens. In a retrospective study, cerebrospinal fluid and acute-phase serum paired samples from 108 patients were tested by the MAC-EIA and by an IgM immunofluorescence assay. The results were compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Serum canine distemper virus (CDV) titers were consistent with current vaccination. 16 Although enzyme-linked immunosorbent assay, IFA, serum neutralization, and complement fixation tests 15,19,20,24 are commercially available with anti-human LACV antibodies, a no such tests are available for anti-dog antibodies to LACV. Creation of an anti-dog antibody was attempted but not successful.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Serum canine distemper virus (CDV) titers were consistent with current vaccination. 16 Although enzyme-linked immunosorbent assay, IFA, serum neutralization, and complement fixation tests 15,19,20,24 are commercially available with anti-human LACV antibodies, a no such tests are available for anti-dog antibodies to LACV. Creation of an anti-dog antibody was attempted but not successful.…”
mentioning
confidence: 99%
“…It had been suggested that LaCrosse viremias are transient and antibody titers and virus (as with other encephalitic viruses) may be sequestered in the CSF. 15,20,37,38 For this reason, cases positively diagnosed with LACV encephalitis by immunohistochemistry (IHC) have produced negative serologic results. 28 Corticosteroid therapy used in this case may have also had an effect on the attenuation of an antibody response.…”
mentioning
confidence: 99%
“…Intrathecal production of virus-specific antibodies can also be used for the early diagnosis of viral infection in the central nervous system. Demonstration of a relative increase in total virus-specific antibody levels or the presence of virus-specific IgM-class antibodies in the cerebrospinal fluid (CSF) has been used to diagnose other viral infections in the central nervous system (2,3,6,8,12,13). A positive result is considered to document a causal relationship between infection and disease.…”
mentioning
confidence: 99%